Crustal radial anisotropy shear wave velocity of SE Tibet from ambient noise tomography - Li, Zhengyang (2023)
We present a high-resolution 3-D radial anisotropy shear wave crustal model of SE Tibet by jointly inverting Rayleigh and Love dispersion curves from ambient noise recorded by CHINArray Phase I network. Our crustal shear wave model displays similar velocity features as the previous studies. Our radial anisotropy model reveals new information of radial anisotropy in the crust, implying different deformation patterns operating in the crust. Widespread positive radial anisotropy (Vsh > Vsv) is imaged in the crust across most of our study areas, which could result from the sub-horizontal aligned crustal materials caused by the ductile deformation and expansion of the Tibetan Plateau. Negative radial anisotropy is observed in the crust of the northern and central segments of the Xiaojiang fault (XJF). However, only the upper crust in the southern segment is imaged as the negative radial anisotropy. We consider vertical alignments of the cracks, faults and the crustal minerals in the middle and upper crust are the origin of the negative radial anisotropy. This pattern is also associated with the activities of the XJF and further implies the deformation mechanism is different between the segments. Neutral radial anisotropy is observed in the inner zone of Emeishan Large Igneous Province, which can be attributed to the equilibrium of the horizontal sills and the vertical dikes of the magma system. Our model provides new insights into the deformation pattern of SE Tibet.